Supplementation of l‐arginine boosts the therapeutic efficacy of anticancer chemoimmunotherapy. Issue 7 (12th June 2020) - Satoh, Yusuke; Kotani, Hitoshi; Iida, Yuichi; Taniura, Takahito; Notsu, Yoshitomo; Harada, Mamoru
Abstract: Myeloid‐derived suppressor cells (MDSCs) play a crucial role in immunosuppression in tumor‐bearing hosts. MDSCs express arginase‐I and indoleamine 2, 3‐dioxygenase; they suppress T‐cell function by reducing the levels of l ‐arginine and l ‐tryptophan, respectively. We examined the anticancer effects of supplementation of these amino acids in CT26 colon carcinoma‐bearing mice. Oral supplementation of l ‐arginine or l ‐tryptophan (30 mg/mouse) did not affect tumor growth, whereas oral supplementation of d ‐arginine was lethal. Supplementation of l ‐arginine showed a tendency to augment the efficacy of cyclophosphamide (CP). CP reduced the proportions of granulocytic MDSCs and increased the proportions of monocytic MDSCs in the spleen and tumor tissues of CT26‐bearing mice. l ‐Arginine supplementation alone did not affect the MDSC subsets. CP treatment tended to reduce the plasma levels of l ‐arginine in CT26‐bearing mice and significantly increased the number of tumor‐infiltrating CD8 + T cells. In addition, l ‐arginine supplementation significantly increased the proportions of tumor peptide‐specific CD8 + T cells in draining lymph nodes. Importantly, additional supplementation of l ‐arginine significantly increased the number of cured mice that were treated with CP and anti‐PD‐1 antibody. Totally, l ‐arginine supplementation shows promise for boosting the therapeutic efficacy of chemoimmunotherapy. Abstract : Combination treatment with cyclophosphamide and anti‐PD‐1 antibody significantly suppressed the tumor growth, but did not exert a curative effect. However, the addition of l ‐arginine supplementation boosted to complete regression in the majority of mice.